SPEECH ACTS ON EFL LEARNERSâ TEACHING PERFORMANCE AND ITS IMPLICATION IN TEACHING AND LEARNING ACTIVITY - Zulianti, Hajjah (JURNAL SMART, 2018)
This research attempts to find the classification of speech acts and its implication in teaching and learning activity. The researcher uses observation and recording technique to collect the data. In analyzing the data, the researcher uses descriptive qualitative method. It was found that there are two types of speech acts: direct and indirect speech acts. It is categorized into four: representative, expressive, directive, commissive. The use of speech acts gives some implications: improving studentsâ understanding of speech acts, increasing level of decency in a communication, improving class atmosphere and studentsâ motivation, and building good relationship between teacher and students. Â Keywords: Speech acts, EFL Teaching Performance